Photo/thermoresponsive ABC triblock copolymer-based ion gels: photoinduced structural transitions. Issue 45 (17th September 2018) - Tamate, Ryota; Usui, Ryoji; Hashimoto, Kei; Kitazawa, Yuzo; Kokubo, Hisashi; Watanabe, Masayoshi
Abstract : Photo-induced hardening/softening of an ion gel formed by an ABC triblock copolymer was realized. Abstract : A photo/thermoresponsive ABC triblock copolymer-based ion gel exhibiting photoinduced structural transitions accompanied by significant rheological changes is newly developed. The ABC triblock copolymer comprises an ionic liquid (IL)-phobic A block, an IL-philic B block, and a photo/thermoresponsive C block containing azobenzene moieties. The IL-phobic A block forms a rigid micellar core in an IL over a wide temperature range and the photo/thermoresponsive C block undergoes upper critical solution temperature (UCST)-type phase transition in ILs. In concentrated polymer solution, the ABC triblock copolymer can form a percolated micellar network at low temperatures through aggregation of A and C blocks as physical crosslinks, bridged by IL-philic B blocks. In contrast, the ion gel undergoes structural transition to jammed micelles at high temperatures due to the disassembly of the thermoresponsive C block, resulting in significant softening of the ion gel. Importantly, the temperature dependences of the viscoelastic properties of the ion gel differ drastically depending on photo-irradiation conditions as the photoinduced isomerization of azobenzene moieties in the C block modulates the affinity between the polymer chain and IL. Utilizing this feature, photoinduced softening/hardening of the ion gel is realized at constant temperature. This study provides a promising strategy to control the rheological properties of nonvolatile soft materials via contactless light irradiation that could be exploited in various applications such as photoresponsive soft actuators and photo-healable soft materials.